2022
DOI: 10.3389/fmolb.2021.800819
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Residue-specific Contributions to Binding and Thermal Stability Using Yeast Surface Display

Abstract: Accurate prediction of residue burial as well as quantitative prediction of residue-specific contributions to protein stability and activity is challenging, especially in the absence of experimental structural information. This is important for prediction and understanding of disease causing mutations, and for protein stabilization and design. Using yeast surface display of a saturation mutagenesis library of the bacterial toxin CcdB, we probe the relationship between ligand binding and expression level of dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(77 citation statements)
references
References 75 publications
(110 reference statements)
0
77
0
Order By: Relevance
“…Different populations of SSSM libraries were sorted based on the expression and binding histograms of the libraries (Supporting Figure S2). Populations were subjected to deep sequencing and the mean fluorescence intensities of binding (MFI seq (bind)) and expression (MFI seq (expr)) were estimated as described (22). Values of normalized MFI seq (bind) and normalized MFI seq (expr) were used to predict stabilized mutants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different populations of SSSM libraries were sorted based on the expression and binding histograms of the libraries (Supporting Figure S2). Populations were subjected to deep sequencing and the mean fluorescence intensities of binding (MFI seq (bind)) and expression (MFI seq (expr)) were estimated as described (22). Values of normalized MFI seq (bind) and normalized MFI seq (expr) were used to predict stabilized mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly none of the suppressors were found at the residues directly involved in GyrA binding. In any case, we have recently shown that such active-site residues can be identified based on the pattern of MFI seq (bind) and MFI seq (expr) in deep mutational scanning libraries and removed from the set of putative global suppressors (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations